Women's knowledge about risk factors, prevention and diagnostics of cervical precancerous changes at colposcopy clinic in Latvia - Ungure, Anita; Žodžika, Jana; Lietuviete, Nellija; Rezeberga, Dace; Šenfelde, Ilva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The incidence of cervical cancer in Latvia is one of the highest among European countries. An organized cervical cancer screening program in Latvia was introduced in 2009. Women’s knowledge and attitude regarding cervical cancer is the key component for successful prevention of this disease. The aim of this study was to evaluate women’s knowledge about the risk factors, prevention and diagnostic methods of precancerous and invasive disease of the uterine cervix in the main colposcopy clinic in Latvia and to compare women's knowledge before and after their first colposcopy visit. Methods: This was a cross sectional study where 100 women were included while attending their first colposcopy visit at Colposcopy Clinic of Riga East Clinical University Hospital. Study was performed in the period September 2017 to November 2017. Exclusion criteria were colposcopy follow-up examination and pregnancy. The most common reason for a planned colposcopy was suspected precancerous changes during cytology testing. Results: The most common information resources regarding reproductive health were gynaecologist (79%) and mass media (51%). Women knowledge about the risk factors of cervical precancerous changes were as follows: 30% marked smoking and 26% - early onset of the first sexual intercourse. 31% of women knew that vaccination against HPV is an effective prevention. 53% of women considered cervical cytology and 52% - colposcopy as a diagnostic method for precancerous changes. Higher number of women evaluated their general knowledge as sufficient after the visit (10% vs. 30%, p<0.05), but only smoking as a risk factor was recognized significantly more often (30% vs. 42%, p<0.05). Conclusions: Although current study presented specific population of women attending Colposcopy clinic because of suspected precancerous disease, less than a half of women knew risk factors, prevention and diagnostics of these changes. Overall women were satisfied with information they received during their first colposcopy visit, but afterward only knowledge about smoking as a possible risk factor improved significantly. It is important to improve women's knowledge about the meaning of prevention methods in order to increase the awareness of cervical cancer in Latvia.